2018
DOI: 10.1093/ofid/ofy300
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Bloodstream Infections Caused by Escherichia coli and Klebsiella pneumoniae That Are Piperacillin-Tazobactam-Nonsusceptible but Ceftriaxone-Susceptible

Abstract: BackgroundPiperacillin-tazobactam-nonsusceptible (TZP-NS) Enterobacteriaceae are typically also resistant to ceftriaxone. We recently encountered bacteremias due to Escherichia coli (Ec) and Klebsiella pneumoniae (Kp) that were TZP-NS but ceftriaxone-susceptible (CRO-S).MethodsWe reviewed all Ec and Kp bacteremias from 2011 to 2015 at our center and assessed the prevalence, antimicrobial susceptibilities, genetic profiles, patient characteristics, treatments, and outcomes of TZP-NS/CRO-S infections. We identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
15
1
Order By: Relevance
“…Although, the exact mechanism of amplification/hyperproduction has remained elusive. Due to the emergence of a TZP-resistant but 3rd generation cephalosporins and carbapenems susceptible E. coli and K. pneumoniae phenotype 12 14 , as well as the increasing reliance on TZP as an empirical treatment 6 and the recent interest in the use of TZP as a carbapenem sparing treatment for extended-spectrum β-lactamase infections 33 , 34 , it is of growing importance to understand the mechanism of amplification. In this study we had the opportunity to compare a pair of clonal isolates which have evolved within a patient to become TZP-resistant but remain cephalosporin/carbapenem susceptible, allowing us to build on recent studies and identify the mechanism of IS 26 -mediated amplification of bla TEM-1B which leads to TZP-resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, the exact mechanism of amplification/hyperproduction has remained elusive. Due to the emergence of a TZP-resistant but 3rd generation cephalosporins and carbapenems susceptible E. coli and K. pneumoniae phenotype 12 14 , as well as the increasing reliance on TZP as an empirical treatment 6 and the recent interest in the use of TZP as a carbapenem sparing treatment for extended-spectrum β-lactamase infections 33 , 34 , it is of growing importance to understand the mechanism of amplification. In this study we had the opportunity to compare a pair of clonal isolates which have evolved within a patient to become TZP-resistant but remain cephalosporin/carbapenem susceptible, allowing us to build on recent studies and identify the mechanism of IS 26 -mediated amplification of bla TEM-1B which leads to TZP-resistance.…”
Section: Discussionmentioning
confidence: 99%
“…A phenotype in Klebsiella pneumoniae and E. coli clinical isolates has emerged which has been classified as TZP-non-susceptible but susceptible to 3rd generation cephalosporins and carbapenems 12 14 , indicating a different resistance mechanism. While still relatively rare, one study in the United States found that the frequency of this phenotype was between 1.9 and 5.6% of E. coli and K. pneumoniae isolated from the bloodstream between 2011 and 2015, and specifically 4.1% of all E. coli over the study period 14 . The same study reported that risk factors associated with the TZP-non-susceptible but 3rd generation cephalosporin and carbapenem susceptible phenotype included exposure to β-lactam/β-lactamase inhibitors and cephalosporins within the previous 30 days 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, among CTX-M-CA-np E. coli and K. pneumoniae , 10.1% ( n =15) that were classified as AmpC/ESBL-np showed in vitro TZP resistance and third-generation cephalosporin susceptibility. These strains were considered an emerging cause of BSI [ 25 ] and were the target of phenotypic and genotypic characterization [ 26 ] that did not fully elucidate the underlying resistance mechanism, even though they showed TZP activity on a murine model. Due to limited evidence on its generalizability to clinical practice, further studies are needed before considering TZP as a valid option against these strains in BSI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the concentration of tazobactam alongside a fixed dose of piperacillin has also rescued TZP effectiveness against TEM-1 hyperproducers in a neutropenic mouse model (25), and could be a viable strategy to protect its future effectiveness. It is worth noting observational clinical data (51), and in vivo experimental data (52), suggesting TZP may be effective against some organisms with in vitro phenotypic resistance to TZP.…”
Section: Discussionmentioning
confidence: 99%